KARTU UMKM SEJAHTERA (KUS): PRODUK PERBANKAN SYARIAH SEBAGAI MEDIA MENGEMBANGKAN UMKM INDONESIA SECARA INKLUSIF - Ervan Hemawan; Efrilia Sari; Azizatul Umro (Kompetensi (Competence : Journal of Management Studies), 2017)
Small and medium enterprise (SMEs) is a sector that has an important role in national economic development. In addition, the development of SMEs from 2010-2013 always experienced a significant increase. However, there are still internal and external constraints experienced by UMKM in developing it. The presence of sharia banking in Indonesia is very suitable as a medium for developing small and medium enterprises (SMEs). Profit sharing system is very profitable and not too burdensome like a conventional bank in general. However, the provision of capital based on sharia principles is not sufficient in developing SMEs. Therefore, a program is needed to develop and grow SMEs from sharia banking in order to attract SMEs producers to use sharia banking services. The program is a prosperous SMEs card (KUS). The concept of KUS is to develop Islamic banking products that already exist, namely mudaraba and musharaka by adding business coaching facilities. The stakeholders (stakeholders) in running the program KUS to materialize is sharia banking, academics or practitioners, local governments and manufacturers of SMEs. When KUS program and all stakeholder parties work together well. So, it will have an impact on: raising awareness for entrepreneurship by forming new SMEs, optimizing SMEs, increasing number of producer of SMEs (customer) in sharia banking. Thus, it will lead to inclusive growth of SMEs.